Herbage intake, methane emissions and animal performance of steers grazing dwarf elephant grass v. dwarf elephant grass and peanut pastures. (22nd April 2016) - Andrade, E. A.; Almeida, E. X.; Raupp, G. T.; Miguel, M. F.; de Liz, D. M.; Carvalho, P. C. F.; Bayer, C.; Ribeiro-Filho, H. M. N.
Abstract : Management strategies for increasing ruminant legume consumption and mitigating methane emissions from tropical livestock production systems require further study. The aim of this work was to evaluate the herbage intake, animal performance and enteric methane emissions of cattle grazing dwarf elephant grass (DEG) ( Pennisetum purpureum cv. BRS Kurumi) alone or DEG with peanut ( Arachis pintoi cv. Amarillo). The experimental treatments were the following: DEG pastures receiving nitrogen fertilization (150 kg N/ha as ammonium nitrate) and DEG intercropped with peanut plus an adjacent area of peanut that was accessible to grazing animals for 5 h/day (from 0700 to 1200 h). The animals grazing legume pastures showed greater average daily gain and herbage intake, and shorter morning and total grazing times. Daily methane emissions were greater from the animals grazing legume pastures, whereas methane emissions per unit of herbage intake did not differ between treatments. Allowing animals access to an exclusive area of legumes in a tropical grass-pasture-based system can improve animal performance without increasing methane production per kg of dry matter intake.